2017
DOI: 10.1177/1934578x1701200101
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antileishmanial Components from the Bark Extract of Ruyschia phylladenia from Monteverde, Costa Rica

Abstract: The bark of Ruyschia phylladenia was collected from Monteverde, Costa Rica, and extracted with acetone. Bioactivity-directed chromatographic separation of the crude acetone bark extract of R. phylladenia led to isolation and identification of lupeol, betulinic acid, and isofraxidin. Lupeol and betulinic acid showed in-vitro cytotoxic activity to MCF-7, MDA-MB-231, and 5637 human tumor cell lines. Isofraxidin was not cytotoxic, but did show antileishmanial activity to Leishmania amazonensis promastigotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Artemisia incisa Asteraceae aerial parts [56] Artemisia abrotanum Asteraceae aerial parts [57] Artemisia keiskeana Asteraceae whole plant [58] Artemisia scoparia Asteraceae aerial parts [59] Artemisia selengensis Asteraceae aerial parts [60] Impatiens balsamina Balsaminaceae root [61] Chimonanthus salicifolius Calycanthaceae aerial parts [62] Chloranthus anhuiensis Chlorantaceae whole plant [63] Chloranthus japonicus Chlorantaceae root [39] Daboecia cantabrica Ericaceae flower [21] Erica spp Ericaceae flower [21] Euphorbia lagascae Euphorbiaceae seed [64] Fraxinus exelsior Oleaceae bark [65] Fraxinus japonicus Oleaceae bark [66] Fraxinus ornus Oleaceae bark, flowers, leaves [67] Greenea corymbose Rubiaceae stem bark, leaves [43] Greenea montana Rubiaceae stem bark, root bark, leaves [43] Ixora cibdela Rubiaceae stem bark, root bark [68] Ixora javanica Rubiaceae stem bark, root bark [43] Morus alba Moraceae leaves [69] Micrandra elata Euphorbiaceae twig [70] Pelargonium reniforme Geraniaceae root [71] Peucedanum praeruptorum Apiaceae root [72] Rhododendron rubiginosum Ericaceae leaves [73] Ruyschia phylladenia Marcgraviaceae bark [29] Saposhnikovia divaricata Apiaceae root [74] Sarcandra glabra Chloranthaceae whole plant [75] Sapium discolor Euphorbiaceae stem, leaves [76] Solanum indicum Solanaceae seed [77] 2.…”
Section: Genus and Species Family Part(s)mentioning
confidence: 99%
See 4 more Smart Citations
“…Artemisia incisa Asteraceae aerial parts [56] Artemisia abrotanum Asteraceae aerial parts [57] Artemisia keiskeana Asteraceae whole plant [58] Artemisia scoparia Asteraceae aerial parts [59] Artemisia selengensis Asteraceae aerial parts [60] Impatiens balsamina Balsaminaceae root [61] Chimonanthus salicifolius Calycanthaceae aerial parts [62] Chloranthus anhuiensis Chlorantaceae whole plant [63] Chloranthus japonicus Chlorantaceae root [39] Daboecia cantabrica Ericaceae flower [21] Erica spp Ericaceae flower [21] Euphorbia lagascae Euphorbiaceae seed [64] Fraxinus exelsior Oleaceae bark [65] Fraxinus japonicus Oleaceae bark [66] Fraxinus ornus Oleaceae bark, flowers, leaves [67] Greenea corymbose Rubiaceae stem bark, leaves [43] Greenea montana Rubiaceae stem bark, root bark, leaves [43] Ixora cibdela Rubiaceae stem bark, root bark [68] Ixora javanica Rubiaceae stem bark, root bark [43] Morus alba Moraceae leaves [69] Micrandra elata Euphorbiaceae twig [70] Pelargonium reniforme Geraniaceae root [71] Peucedanum praeruptorum Apiaceae root [72] Rhododendron rubiginosum Ericaceae leaves [73] Ruyschia phylladenia Marcgraviaceae bark [29] Saposhnikovia divaricata Apiaceae root [74] Sarcandra glabra Chloranthaceae whole plant [75] Sapium discolor Euphorbiaceae stem, leaves [76] Solanum indicum Solanaceae seed [77] 2.…”
Section: Genus and Species Family Part(s)mentioning
confidence: 99%
“…The pure IF, isolated from Micrandera elata, also showed cytotoxic activities against murine leukemia (P388, ED50 = 1.7 µg/mL), with no effects on human mouth epidermal carcinoma (KB, ED50 > 100 µg/mL) [70]. Also, Steinberg and co-workers reported that IF, isolated from Ruyschia phylladenia, had no cytotoxicity on cancer cell lines including two lines of human breast adenocarcinoma (MCF-7, MDA-MB-231) and human bladder carcinoma cells with low activity (IC50 = 51.9 µg/mL) on BALB/c mouse macrophages [29].…”
Section: Anticancer and Cytotoxic Activitiesmentioning
confidence: 99%
See 3 more Smart Citations